Digital Government and User Experience: how the combination of evaluation methods can contribute to the improvement of m-gov applications - Melo, Diogo; da Silva, Talita; Monteiro, Ingrid; Sampaio, Andreia; Meireles, Carolina; Braz, Leonara; Cruz, Geórgia; Vasconcelos, Davi (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2022: Anais do XVIII Simpósio Brasileiro de Sistemas de Informação, 2022)
Context: Digital transformation is a reality; Services that used to be face-to-face are now very flexible. With this, the countries chosen by the e-government improve the relationship with the citizens. Problem: Citizen-user systems have their own characteristics and a plurality of development needs and development needs to offer services. Solution: One of the ways to check the quality of computer systems is the Human-Computer Interaction (HCI) estimates, which facilitate the identification and correction of problems that can cause wear and tear in the user's interaction with these systems. IS theory: It was based on the theory of technology acceptance (to the extent that technology accepts), which are important for the use and quality of the application by citizens. Method: We used: Semiotic Inspection Method (communicability), Heuristic Evaluation and Cognitive Path (usability), and MALTU (usability based on user comments in the application store). In addition to their specificities, all of them do not require direct participation from the end user during the process. Summarize: The combined use of the application of methods and problems in the overview of a comparative analysis with a focus on evaluation in applications. Contributions and Impact in the IS area: find yourself in the evaluation of an application that offers a diversity of services and thousands of Ceará users. Considering the challenges in the area, it was concerned with the quality of the interface and interaction. Help in deciding which method is most suitable for evaluating government application.